Pengaruh Akuntabilitas, Transparansi, dan Kualitas Sumber Daya Manusia Terhadap Kinerja Pegawai (Studi Pada Desa Se-Kecamatan Langsa Lama Kota Langsa) - Remilla Sitohang (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to examine the Influence of Accountability, Transparency, and Human Resource Quality on Employee Performance (A Study in the Villages of Langsa Lama Sub-District, Langsa City). The sample selection in this research utilized purposive sampling, with a total of 75 respondents. Data collection was carried out through the distribution of questionnaires. The obtained data were analyzed using the Statistical Product and Service Solutions (SPSS) program. The analytical methods employed in this study included validity testing, classical assumption testing, and multiple linear regression analysis. The research results indicate that accountability significantly influences employee performance, as evidenced by the t-sig value of 0.000 < 0.05. Transparency does not have a significant impact on employee performance, with a t-sig value of 0.130 > 0.05. Human Resource Quality significantly affects employee performance, as indicated by the t-sig value of 0.007 < 0.05. Simultaneously, accountability, transparency, and human resource quality collectively have a significant influence on employee performance, as demonstrated by the results of the F-test with a significance value of 0.000 < 0.05.